Asymmetric Price Adjustment in the Small - Daniel C. Levy; Haipeng (Allan) Chen; Sourav Ray; Mark Bergen (Kiel Institute for the World Economy (IfW), 2007)
Analyzing a large weekly retail transaction price dataset, we uncover a surprising regularity'small price increases occur more frequently than small price decreases for price changes of up to about 10 cents, while there is no such asymmetry for larger price changes. The asymmetry holds for the entire sample and for individual categories. We find that while inflation can explain some of the asymmetry, inflation is not the whole story as the asymmetry holds even after excluding inflationary periods from the data, and even for products whose price had not increased over the eight-year period. The findings hold for different measures of inflation and also after allowing for lagged price adjustments. We offer a consumer-based explanation for these findings.
Keywords: D21; D11; L11; M31; E31; D80; 330; Asymmetric Price Adjustment; Price Rigidity